Physiological Responses to Hypoxia on Triglyceride Levels - Morin, Renée; Goulet, Nicholas; Mauger, Jean-François; Imbeault, Pascal (Frontiers in Physiology, 2021)
Hypoxia is a condition during which the body or specific tissues are deprived of oxygen. This phenomenon can occur in response to exposure to hypoxic environmental conditions such as high-altitude, or as a consequence of pathophysiological conditions such as obstructive sleep apnea. Circumstances such as these can cause a restriction in oxygen supply and/or consumption, leading to oxyhemoglobin desaturation and tissular hypoxia. In certain cases, hypoxia can lead to severe health consequences such as an increased risk of developing cardiovascular diseases, type 2 diabetes, and atherosclerosis. A potential explanation for the link between hypoxia and an increased risk of developing cardiovascular diseases lies in the possible disturbing effect of hypoxia on circulating blood lipids, more specifically its capacity to increase plasma triglyceride concentrations. Increased circulating triglyceride levels result from a production of triglyceride-rich lipoproteins, namely very low-density lipoproteins, and chylomicrons, exceeding their clearance rate. Considerable research in murine models report that hypoxia may have detrimental effects on many aspects of triglyceride metabolism. However, in humans, the mechanisms underlying the disturbing effect of hypoxia on triglyceride levels remain to be clarified. In this mini-review, we report the available evidence on the physiological responses to hypoxia and its impact on circulating triglyceride levels. We discuss mechanisms by which hypoxia affects various organs involved in the metabolism of triglyceride-rich lipoproteins. This information will be beneficial to the scientists or clinicians interested in the hypoxia-regulatory cascades that lead to a deteriorated lipid profile and that significantly increased the risk of developing hypoxia-related health consequences.